The effect of institutional investors on estimation value of financial statements of companies in Tehran Stock Exchange - Shahrzad Taheriyan Sarraf (Atlantic Review of Economics, 2015)
The purpose of this study is to evaluate the effect of institutional investors on the financial statements of the predictive value of listed companies in Tehran Stock Exchange. According to the owners of institutional and professional investors, their presence may cause monitor management. This can lead to profitability rather than focusing on short-term goals, according to the company's long-term value maximization. The study period is from 2006 to 2010 and 85 companies were selected to test the hypothesis. The methodology based on purpose of this research, is applied and based on the correlation between variables is correlation research. Before hypothesis testing and tests to check the validity of data variance anisotropy, Chow test and Hausman test was discussed. The result of statistics with use of combination data shows that institutional investors in ownership instruction is determined as most main mechanism in improvement of financial statements.
Keywords: G15; G17; G32; M40; 330; Institutional Investors; Estimation Value; Ownership Concentration